Triclosan em águas: determinação por UV-Vis associada a calibração multivariada e avaliação da fotodegradação - Silva, Isla Marcolino da (2020)
Emerging contaminants are characterized as non-legislated compounds that have adverse effects on the environment, as well as on humans and are basically divided into three groups: drugs, biocides and pesticides; and personal care products (PHP). PHP is an important group of emerging contaminants, since it is used on a large scale and worldwide. Among them, one of the most used in PHP formulas, is Triclosan (TCS), widely known for its antimicrobial function and for not being completely eliminated in sewage treatment plants. Due to the large-scale use of TCS and the possible effects caused by its insertion in the environment, the study presented here proposed to apply a treatment for the removal of this biocide, through optimized direct photolysis, based on complete factorial plans, on seawater and river. These treatments were evaluated through phytotoxic effects with lettuce seeds (Lactuca Sativa), as a test organism. The determination of TCS concentrations, was carried out by UV absorbance measurements at 280nm and the data treated with multivariate calibration models by regression of the principal components. Photodegradation using both ultraviolet radiation (UVA) and sunlight, combined with planning variables (pH, exposure time and type of radiation) was observed. The treatments made from the factorial design showed to be more efficient when compared to the process of direct photolysis only with UVA light and sunlight, since all the variables analyzed were significant. Phytotoxicity tests indicated that TCS at a concentration of 1mg L-1, without photolysis inhibited the relative growth of lettuce seed root by 27%. When the seeds were exposed to the solutions resulting from river water treatments, there was no change in root growth. Assays with seawater, there was no germination, probably due to the high salt concentration.These data indicate that there was no generation of phytotoxic products after photodegradation The multivariate calibration models developed and validated for TCS samples in sea and river water allowed the construction of calibration models by regression of the main components, being an alternative of analysis to conventional methods.